Short duration combination chemotherapy in the treatment of small cell lung cancer. Issue 9 (September 1986) - Dorward, A J; Banham, S W; Hutcheon, A W; Ahmedzai, S; Cunningham, D; Gregor, A; Soukop, M; Stack, B H; Mackay, N S; Kaye, S B
Abstract : Ninety five patients (57 with limited disease and 38 with extensive disease) with previously untreated small cell lung cancer were entered into a study of short duration combination chemotherapy with intravenous cyclophosphamide (750 mg/m2) on day 1, adriamycin (40 mg/m2) on day 1, and etoposide VP-16 (100 mg/m2) on days 1, 2, and 3, with the addition on day 10 of methotrexate 50 mg/m2 with folinic acid rescue and vincristine 2 mg. The treatment was repeated on day 22 and only three courses were given. No maintenance chemotherapy was given, though patients with a complete response received radiotherapy (30-40 Gy (3000-4000 rads] to the primary site in most cases. Forty nine patients (86%) with limited disease achieved a response, with 26 (46%) complete remissions. Twenty five patients (66%) with extensive disease had a response, but only eight (21%) had a complete response. Actuarial survival analysis for the whole patient population showed a median survival of 13 months for patients with limited disease and seven months for those with extensive disease. The median survival was 14 months for those patients with limited disease who achieved a complete response, but only 10 months for non-responders. Myelosuppression was the major expression of toxicity. There were three deaths related to treatment and seven patients had febrile episodes during neutropenia that required antibiotics. Mucositis, which was usually mild, occurred in 49% of patients. The primary site was the main site of initial relapse in 56% of the patients who relapsed. Among patients with limited disease who achieved a complete response, relapses at the primary site were less common in those who received radiotherapy (five out of 12) than in those who did not (all eight). The results indicate that this short duration chemotherapy in small cell lung cancer gives response rates and the potential for long term survival similar to those obtained in other series while allowing patients the maximum time free from treatment.